Juridical Analysis Of The Effectiveness Of The Golden Visa Policy In Improving The Level Of Compliance With Immigration Regulations From The Perspective Of Immigration Law And Administration (A Research Study In Batam City) - Alcer Sanny Maruli Paima Tua; Darwis Anatami; Bachtiar Simatupang; Erniyanti Erniyanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The Golden Visa policy is one of the strategic instruments within Indonesia’s immigration system, aimed at attracting foreign investors by granting long-term residency rights based on a particular investment value. Its implementation is regulated by Law No. 6 of 2011 on Immigration, Government Regulation No. 40 of 2023, Ministry of Law and Human Rights Regulation No. 22 of 2023, and Ministry of Immigration Regulation No. 3 of 2025. This research is motivated by the importance of examining the effectiveness of the policy in increasing compliance with immigration regulations, especially in Batam City, a strategic border area with high foreign investor mobility. This research aims to analyze the Golden Visa policy's legal regulations, assess the effectiveness of its implementation in improving compliance with immigration regulations from a legal and administrative perspective, identify obstacles, and formulate relevant solutions. The methods used are normative and empirical juridical approaches, supported by primary data from interviews and observations at the Batam Immigration Office and secondary data from legal literature and relevant regulations. The research results indicate that although the legal framework for the Golden Visa has been systematically established, there are still weaknesses in the synchronization of norms and the technical guidelines for its implementation. On the implementation side, this policy has contributed to improved administrative compliance by foreign investors; however, challenges remain in the form of structural obstacles, legal culture, and supervisory capacity. Therefore, regulatory improvements, enhanced legal literacy for visa holders, administrative service reforms, and synergy among relevant agencies are needed to ensure that the effectiveness of this policy operates optimally within the corridors of justice, certainty, and legal benefit.